HT–MP metamorphism in Central Qilian Block, NE Tibet Plateau: Implications on the tectonic evolution of the Qilian Orogen. Issue 3 (25th November 2022) - Sun, Yi; Niu, Manlan; Yan, Zhen; Palin, Richard M.; Li, Xiucai; Li, Chen
Abstract : The metamorphism of the Central Qilian Block in the northeastern Tibetan Plateau records a complete tectonic history of the Qilian Orogen. Here, results of structural measurements, geochronological data, and thermobarometry for metamorphic rocks in the Central Qilian Block were presented, which trace the tectonic evolution of the Qilian Orogen. New U–Pb dating of detrital zircon from one paragneiss shows a main age population between c . 1500 and c . 1250 Ma, with the youngest age of 1085 Ma. This unit was intruded by an orthogneiss which has a U–Pb weighted mean age of 920 ± 18 Ma. Together with c . 1200–1000 Ma ages from inherited zircon cores in amphibolites, these results indicate that the protoliths of the Huangyuan Group were formed during the Mesoproterozoic and Neoproterozoic. Rims of these zircons obtain tightly constrained and concordant ages ranging from c . 459 to c . 427 Ma, with a weighted mean age of c . 450 Ma. Phase equilibrium modelling and conventional thermobarometry jointly indicate high‐temperature/medium‐pressure HT–MP metamorphism along a clockwise pressure–temperature ( P–T ) path at c . 450 Ma, passing through prograde conditions of 7.8–8.0 kbar and 620–650°C to peak conditions of ~7 kbar and ~780–800°C. Together with documented widespread metamorphism, magmatism, and ductile shear belts, these new results reassert that the Central Qilian Block experienced a three‐stage tectono‐metamorphic evolution during the Early Palaeozoic and the HT–MP metamorphism of Huangyuan Group was developed by a continental collision geodynamic setting with coeval mafic and granitic magmatism. Abstract : New results for petrology, P–T pseudosection modelling and conventional thermobarometry, geochemistry, and zircon U–Pb dating of the Huangyuan group in the Central Qilian Block were reported. These new results reassert that the Central Qilian Block experienced a three‐stage tectono‐metamorphic evolution during the Early Palaeozoic.